Gossypin mitigates oxidative damage by downregulating the molecular signaling pathway in oleic acid‐induced acute lung injury - Dincer, Busra; Cinar, Irfan; Erol, Huseyin Serkan; Demirci, Beste; Terzi, Funda (Wiley, 2023)
AbstractOne of the leading causes of acute lung injury, which is linked to a high death rate, is pulmonary fat embolism. Increases in proinflammatory cytokines and the production of free radicals are related to the pathophysiology of acute lung injury. Antioxidants that scavenge free radicals play a protective role against acute lung injury. Gossypin has been proven to have antioxidant, antimicrobial, and anti‐inflammatory properties. In this study, we compared the role of Gossypin with the therapeutically used drug Dexamethasone in the acute lung injury model caused by oleic acid in rats. Thirty rats were divided into five groups; Sham, Oleic acid model, Oleic acid+Dexamethasone (0.1 mg/kg), Oleic acid+Gossypin (10 and 20 mg/kg). Two hours after pretreatment with Dexamethasone or Gossypin, the acute lung injury model was created by injecting 1 g/kg oleic acid into the femoral vein. Three hours following the oleic acid injection, rats were decapitated. Lung tissues were extracted for histological, immunohistochemical, biochemical, PCR, and SEM imaging assessment. The oleic acid injection caused an increase in lipid peroxidation and catalase activity, pathological changes in lung tissue, decreased superoxide dismutase activity, and glutathione level, and increased TNF‐α, IL‐1β, IL‐6, and IL‐8 expression. However, these changes were attenuated after treatment with Gossypin and Dexamethasone. By reducing the expression of proinflammatory cytokines and attenuating oxidative stress, Gossypin pretreatment provides a new target that is equally effective as dexamethasone in the treatment of oleic acid‐induced acute lung injury.
Keywords: 3. Good health